2014
DOI: 10.3389/fimmu.2014.00244
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune System and Preeclampsia

Abstract: Normal pregnancy is considered as a Th2 type immunological state that favors an immune-tolerance environment in order to prevent fetal rejection. Preeclampsia (PE) has been classically described as a Th1/Th2 imbalance; however, the Th1/Th2 paradigm has proven insufficient to fully explain the functional and molecular changes observed during normal/pathological pregnancies. Recent studies have expanded the Th1/Th2 into a Th1/Th2/Th17 and regulatory T-cells paradigm and where dendritic cells could have a crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 93 publications
5
99
0
Order By: Relevance
“…There are also findings that excessive activation of the innate immune system promotes the etiopathology of PE (134). Immunohistochemical studies revealed that there is increased expression of the CD14 macrophage marker in the decidua basalis from preterm preeclamptic versus preterm control pregnancies (157).…”
Section: Mice (Having Nk Cells But Not T or B Lymphocytes) Into Balb/mentioning
confidence: 99%
“…There are also findings that excessive activation of the innate immune system promotes the etiopathology of PE (134). Immunohistochemical studies revealed that there is increased expression of the CD14 macrophage marker in the decidua basalis from preterm preeclamptic versus preterm control pregnancies (157).…”
Section: Mice (Having Nk Cells But Not T or B Lymphocytes) Into Balb/mentioning
confidence: 99%
“…9 During normal pregnancy, there is a shift toward T h 2 immunity that results in the synthesis of IL4, IL5, IL6, and IL10, whereas in PE there is a distinct shift toward T h 1 immunity, resulting in the production of IL2, TNFα, and IFNγ. 54 It is this shift toward T h 1-associated immunity in PE that results in the exaggerated MSIR. Therefore, T h 1-and T h 2-associated cytokines have gained interest as potential PE biomarkers.…”
Section: Cytokinesmentioning
confidence: 99%
“…Although there have been great advances in medicine, the frequency of this disease has not been successfully modified significantly (3). Currently, the etiology of this disease remains unknown, therefore, in order to explain its origin various theories have been raised, and within each of them the genetic origin, immune factor, endothelial dysfunction, increased oxidative stress, micronutrients deficiency, among others, can be mentioned (3)(4)(5)(6)(7)(8). During pregnancy, there is a normal increase in the production of reactive oxygen species (ROS); likewise, the antioxidant capacity is increased.…”
Section: Introductionmentioning
confidence: 99%